2018
DOI: 10.3389/fnmol.2018.00181
|View full text |Cite
|
Sign up to set email alerts
|

Key Genes and Pathways Associated With Inner Ear Malformation in SOX10 p.R109W Mutation Pigs

Abstract: SRY-box 10 (SOX10) mutation may lead to inner ear deformities. However, its molecular mechanisms on inner ear development are not clear. In this work, the inner ear morphology was investigated at different embryonic stages of the SOX10 mutation miniature porcine model with sensorineural hearing loss, and high-throughput RNA-seq and bioinformatics analyses were applied. Our results indicated that the SOX10 mutation in the miniature pigs led to an incomplete partition (IP) of the cochlea, a cystic apex caused by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 38 publications
(48 reference statements)
1
18
0
Order By: Relevance
“…Thus, these large animal models may extend translational proof-of-principle studies. China has established the largest pool of pig models and a large amount of mutations have been generated [ 52 , 53 ]. Interestingly, the mutation of SOX10 (R109W) in pigs by N-ethyl-N-nitrosourea mutagenesis causes inner ear malfunctions and hearing loss [ 52 ], and might represent a good model to test the gene therapy approach for hearing loss.…”
Section: Large Animal Models For Hearing Researchmentioning
confidence: 99%
“…Thus, these large animal models may extend translational proof-of-principle studies. China has established the largest pool of pig models and a large amount of mutations have been generated [ 52 , 53 ]. Interestingly, the mutation of SOX10 (R109W) in pigs by N-ethyl-N-nitrosourea mutagenesis causes inner ear malfunctions and hearing loss [ 52 ], and might represent a good model to test the gene therapy approach for hearing loss.…”
Section: Large Animal Models For Hearing Researchmentioning
confidence: 99%
“…Further localization was carried out in 10 mutation families, and mutation of the SOX10 (R109W) gene was found to cause abnormal inner ear function similar to human Mondini malformation. Hao et al. (2018) studied the molecular mechanism of inner ear development in miniature pigs with Sox10 mutation and sensorineural deafness and found that Sox10 mutation resulted in incomplete partition of the cochlea, cystic apex, and cochlear defect and shortening.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study showed that SOX10 mutation will cause both hair cell and SC loss in a heterozygous Dom mouse model [ 15 ]. In pigs, shorter cochlear conduct was induced by SOX10 p.Arg109Trp missense mutation [ 28 ]. There are complex regulatory networks between SCs and hair cells [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%